Evaluation of aerosol loading and its relationship with geopotential height in Nigeria’s Guinea Coast - Onyinyechi Caroline Ibe; Okechukwu Kelechi Nwofor; Ugochukwu Kingsley Okoro (Bulletin of the National Research Centre)
Abstract Climate variability and atmospheric changes significantly affect weather patterns and human activities. Aerosols impact the Earth's climate by influencing cloud formation, scattering radiation, and cooling the planet. However, aerosols, like black carbon, absorb and reemit radiation, contributing to global warming. This study aims to assess aerosol optical depth (AOD) over Nigeria's Guinea Coast, compare aerosol loading across the region, examine the relationship between aerosol loading and geopotential height, and explore the impact of meteorological variables on aerosol levels. AOD data were sourced from MODIS, while geopotential height and meteorological data was obtained from MERRA-2. The study found significant aerosol loading during the dry season, particularly along the coastal region (Lagos, Warri, and Port Harcourt), and lower AOD during the wet season. Geopotential height values were higher during the wet season, especially at 1000-hPa and 850-hPa. A positive correlation was found between AOD and geopotential height. Wind speeds were higher in the north and along the coast, with specific humidity at 1000-hPa directly correlating with geopotential height and inversely with wind speed. The study also showed that the annual AOD distribution mirrors geopotential height patterns at 1000-hPa, with higher values in southern Nigeria. In conclusion, aerosol loading is higher during the dry season, particularly in coastal regions and at lower atmospheric levels. The study highlights how seasonal changes and geographical factors influence aerosol distribution. It also shows that geopotential height strongly affects aerosol concentration, with higher heights linked to increased AOD. This underscores the importance of surface-level aerosols for human health, agriculture, and visibility, and suggests that geopotential height influences where aerosol loading is highest.